Positive psychology in sport and physical activity an introduction - Brady, Abbe; Grenville-Cleave, Bridget (Routledge, 2018)
"Positive psychology (PP) is a fast-developing area of research that emphasises personal growth and the positive qualities of life. This is the first book to apply the principles and practice of PP to sport and physical activity. In attempting to help people enjoy sport, sport psychology has paradoxically often focused on topics such as anxiety, stress and burnout. By contrast, this reader-friendly introduction to PP shows how it can improve sporting performance while also enhancing physical and mental well-being. Demonstrating the practical relevance of PP for all those who participate in sport and physical activity at any level, it covers a variety of topics including: - passion, enjoyment and flow - positive pedagogy and appreciative inquiry for sport leaders, coaches and teachers - gratitude, mindfulness, optimism and hope - positive psychology coaching for sport leaders and practitioners - character strengths, growth mindset and resilience. With expert contributors from around the globe, real-life case studies, practical strategies and suggestions for future research in every chapter, this book is inspirational reading for all students, coaches, researchers and practitioners with an interest in sport and exercise psychology, mental health and well-being"